Dreams about Time - Zaharijević, Adriana (Identities: Journal for Politics, Gender and Culture, 2020)
Author(s): Adriana Zaharijević Title (English): Dreams about Time Journal Reference: Identities: Journal for Politics, Gender and Culture Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 64-65 Page Count: 2 Citation (English): Adriana Zaharijević, “Dreams about Time,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 64-65.